2020
DOI: 10.1186/s12879-020-05662-8
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of SARS-CoV-2 infection among symptomatic healthcare workers in a large university tertiary hospital in São Paulo, Brazil

Abstract: Background Brazil became the epicenter of the COVID-19 pandemic in Latin America since May 2020, reporting the highest number of cases and deaths in the region. Healthcare workers (HCWs) are at increased risk of SARS-CoV-2 infection, experiencing a significant burden from COVID-19. Identifying and understanding the clinical characteristics and risk factors associated with infection are of paramount importance to inform screening strategies and infection control practices in this scenario. The a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 21 publications
1
30
2
7
Order By: Relevance
“…In Brazil, 42.37% of HCWs with symptoms tested positive for COVID-19. In Brazil, over the ten-week study period, the rate of positive testing ranged from 22.2% in the second week to 55.9% in the sixth week, then plateaued to 38–46% 21 . However, much lower percentages of HCWs who had COVID-19 during the study period were reported in China (33.62%) 18 and, in Spain, (11.1%).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, 42.37% of HCWs with symptoms tested positive for COVID-19. In Brazil, over the ten-week study period, the rate of positive testing ranged from 22.2% in the second week to 55.9% in the sixth week, then plateaued to 38–46% 21 . However, much lower percentages of HCWs who had COVID-19 during the study period were reported in China (33.62%) 18 and, in Spain, (11.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients are with or without mild clinical manifestations (4)(5)(6)(7)(8), and the transmission of SARS-CoV-2 from asymptomatic individuals raises the occurrence of COVID-19 and the consequent need for skilled healthcare staff working in the care of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 2113 abstracts were retrieved for screening, 114 full‐text articles were assessed for eligibility, and 50 studies 7 , 8 , 9 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 meeting inclusion criteria were selected in the qualitative synthesis. Data from 49 studies 7 , ...…”
Section: Resultsmentioning
confidence: 99%